2013
DOI: 10.1097/jto.0b013e3182774108
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography RECIST Assessment of Histopathologic Response and Prediction of Survival in Patients with Resectable Non–Small-Cell Lung Cancer after Neoadjuvant Chemotherapy

Abstract: Introduction This study’s objectives were to determine whether tumor response measured by CT and evaluated using Response Evaluation Criteria in Solid Tumors (RECIST) correlated with overall survival (OS) in patients with non-small cell lung cancer (NSCLC) after neoadjuvant chemotherapy and surgical resection. Methods We measured primary tumor size on CT before and after neoadjuvant chemotherapy in 160 NSCLC patients who underwent surgical resection. The relationship between CT-measured response (RECIST) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
95
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 38 publications
8
95
0
2
Order By: Relevance
“…The pathological result revealed that the majority of patients had >80% of residual tumor, but the patient whose tumor size was 3.0 cm with only 20% of residual tumor had no CTCs or CTM in his PV blood. Previous studies have reported that the percentage of viable tumor cells is a significant predictor of overall survival and disease-free survival in patients with neoadjuvant-treated NSCLC, but not in patients who undergo surgery alone (23,24). It can be hypothesized that the neoadjuvant chemotherapy-mediated inhibition of tumor cell metastatic characteristics and changes in the percentage of tumor cells in primary disease reduces CTC shedding into the blood during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological result revealed that the majority of patients had >80% of residual tumor, but the patient whose tumor size was 3.0 cm with only 20% of residual tumor had no CTCs or CTM in his PV blood. Previous studies have reported that the percentage of viable tumor cells is a significant predictor of overall survival and disease-free survival in patients with neoadjuvant-treated NSCLC, but not in patients who undergo surgery alone (23,24). It can be hypothesized that the neoadjuvant chemotherapy-mediated inhibition of tumor cell metastatic characteristics and changes in the percentage of tumor cells in primary disease reduces CTC shedding into the blood during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the metastatic liver nodules after treatment including chemotherapy is of crucial importance which can certainly lead us to earlier and more effective salvage treatment in an attempt to prolong survival. Response Evaluation Criteria in Solid Tumours (RECIST) has become the most frequently used response criteria for solid tumours (William et al, 2013). Nevertheless, there are shortcomings and criticism regarding its use in a number of clinical circumstances such as gastrointestinal stromal tumor (GIST) which has created inevitable inter-observer variability and non-reproducible judgments (Yankelevitz et al, 2000;Reeves et al, 2007;Heussel CP et al, 2007;Benjamin et al, 2007;Plathow et al, 2008;Mantatzis et al, 2009;Galizia et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As RECIST is primarily based on measurement of the longest diameters of the target lesions in the transverse section, it is often a clinical dilemma for radiologists to determine the longest diameters when the target lesions merge to form a conglomerate mass or split into even smaller lesions after treatment (Sohaib et al, 2000;Reiner et al, 2009). Instead, volumetric evaluation (VE) has gained a wider interest and acceptance as an alternative assessment method (Yankelevitz et al, 2000;Winer et al, 2003;Lemke et al, 2006;Vogl et al, 2008;Gavrielides et al, 2009;Frauenfelder et al, 2011;Galizia et al, 2011). An important theoretical advantage of VE is that it offers more accurate measurement and reflection of overall tumor burden in an organ which is with less inter-observer variability and better than the mere measurement of the maximum diameters of up to five indicator lesions per organ (Prasad et al, 2002;Tran et al, 2004;Reiner et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the previous report on MIBC (8), significant association between CT-measured tumor response and OS was observed also in 160 patients with non-small cell lung cancer who received tumor resection following NAC (20). Higher shrinkage, also associated with pathological downstaging as discussed above, facilitates complete resection at RC and also indicates better chemotherapeutic response in the case of post-RC recurrence, both of which seem to contribute to better DSS after RC.…”
Section: Discussionmentioning
confidence: 86%